APPLICATION OF CUSTOMER RELATIONSHIP MANAGEMENT (CRM) TO INCREASE SALES AT UD ULONG PIAN - mutiara tiara; Havid Syafwan Havid; rohminatin iroh (Informatika, Universitas Jenderal Soedirman, 2022)
The development of the business world has entered a new era, where more and more new companies and competing companies in the service,commerce,and manufacturing sectors. The higher the level of customer education, the indirectly the customer will be critical and careful in determining his choice. In this situation, the company should not only rely on the products produced, but the company must also establish a good relationship to every loyal customer then the customer will be loyal to the company. UD Ulong Pian is engaged in sales and services such as the sale of sewing or convection tools, fabrics, home décor equipment and the sale of café tents or tent making services in accordance with customer demand. The problem that occurs in UD Ulong Pian is, the sales process at UD Ulong Pian is still selling conventionally, there are no facilities that help customers to get information, convey assessments of products and also have difficulty in the process of processing and storing customer data that has made buying and selling transactions. This research leverages CRM features that aim to help ud Ulong Pian's service systems attract new customers and retain old customers and expand the sales system. The application is created using php and MySQL programming languages as a database server. With this system is expected to improve the marketing system, sales, service and utilization of Customer Relationship Management has a positive influence on customer loyalty so as to keep customers loyal to UD Ulong Pian.